Atrial appendage closure in patients with heart failure and atrial fibrillation: industry‐independent single‐centre study. (15th November 2021) - Saad, Mohammed; Osman, Mohamed; Hasan‐Ali, Hosam; Abdel Ghany, Mohammed; A Alsherif, Mohamad; Risha, Osama; Sano, Makoto; Fink, Thomas; Heeger, Christian‐Hendrik; Vogler, Julia; Sciacca, Vanessa; Eitel, Charlotte; et al.
Abstract: Aims: To evaluate outcomes of percutaneous left atrial appendage closure (LAAC) in patients with congestive heart failure (CHF) and non‐valvular atrial fibrillation (AF) in a consecutive, industry‐independent registry associated with periprocedural success and complications during long‐term follow‐up. Methods and results: For this analysis, we included patients who underwent transcatheter LAAC from January 2014 to December 2019 at the University Heart Center in Lübeck, Germany, and compared patients with presence of CHF defined as patients with a reduced left ventricular ejection fraction (LVEF ≤ 40%), patients with a mid‐range LVEF (LVEF 41–49%), patients with diastolic dysfunction and preserved LVEF (LVEF ≥ 50%), and patients with right‐sided heart failure and impaired right ventricular function (tricuspid annular plane systolic excursion < 17) to patients undergoing LAAC with no CHF. Primary endpoints were defined as periprocedural complications, and complications during long‐term follow‐up presented as major adverse cardiac and cerebrovascular events (MACCE). A total of 300 consecutive patients underwent LAAC. Of these, 96 patients in the CHF group were compared with 204 patients in the non‐CHF group. Implantation success was lower in CHF group in comparison with non‐CHF group (99.5% vs. 96%, P  = 0.038); otherwise, there were no differences in periprocedural complications between groups. Patients with CHF showed a significantly higher incidence of MACCE rate (31.9% vs. 15.1%, P  = 0.002) and more deaths (24.2% vs. 7%, P  ≤ 0.001) during long‐term follow‐up. In Cox multivariable regression analysis, CHF was an independent predictor of mortality after LAAC implantation at long‐term follow‐up (hazard ratio 3.23, 95% confidence intervals 1.52–6.86, P  = 0.002). Conclusions: Implantation of LAAC devices in patients with non‐valvular AF and CHF is safe. The increased mortality in patients with CHF compared with patients without CHF during the long‐term follow‐up is mainly attributed to comorbidities associated with CHF.